2014
DOI: 10.1371/journal.pone.0088465
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impact of Temperature-Induced Life History Plasticity and Mate Limitation on the Epidemic Potential of a Marine Ectoparasite

Abstract: Temperature is hypothesized to contribute to increased pathogenicity and virulence of many marine diseases. The sea louse (Lepeophtheirus salmonis) is an ectoparasite of salmonids that exhibits strong life-history plasticity in response to temperature; however, the effect of temperature on the epidemiology of this parasite has not been rigorously examined. We used matrix population modelling to examine the influence of temperature on demographic parameters of sea lice parasitizing farmed salmon. Demographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…The 1.5-to 2-year seawater production cycles for farmed salmon add additional variability in host density in coastal regions. [3,59] explain underlying mechanisms [37] project behaviours of systems [20,28,43] predict outcomes of interventions [15,27] raise questions and generate hypotheses [66] propose models [49] present definition functions and goals timescale find possible explanations for patterns and phenomena [18] generate hypotheses [4] specify new data needs [27] [20] regression models -statistical -descriptive/correlational -can include spatial effects GLM, GLMM, random effects, logistic regression -identifying epidemiological factors effecting sea lice abundance on salmon farms [21] -associations between aquaculture and sea louse infections on sea trout [22] survival functions and hazard functions -statistical -descriptive/correlational survival analysis -impacts of sea lice on salmon survival in the NE Atlantic [3] -effects of salinity on sea louse survival on juvenile salmon [23] stochastic processes -discrete-time or continuous-time dynamics [29] rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Outbreak and Transmission Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 1.5-to 2-year seawater production cycles for farmed salmon add additional variability in host density in coastal regions. [3,59] explain underlying mechanisms [37] project behaviours of systems [20,28,43] predict outcomes of interventions [15,27] raise questions and generate hypotheses [66] propose models [49] present definition functions and goals timescale find possible explanations for patterns and phenomena [18] generate hypotheses [4] specify new data needs [27] [20] regression models -statistical -descriptive/correlational -can include spatial effects GLM, GLMM, random effects, logistic regression -identifying epidemiological factors effecting sea lice abundance on salmon farms [21] -associations between aquaculture and sea louse infections on sea trout [22] survival functions and hazard functions -statistical -descriptive/correlational survival analysis -impacts of sea lice on salmon survival in the NE Atlantic [3] -effects of salinity on sea louse survival on juvenile salmon [23] stochastic processes -discrete-time or continuous-time dynamics [29] rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Outbreak and Transmission Dynamicsmentioning
confidence: 99%
“…For example, a modified susceptible-exposed-infective-resistant ordinary differential equation model showed that stronger currents and higher stocking levels increased transmission of sea lice between two hypothetical farms [52]. A matrix model that explicitly accounted for demographic stochasticity among sea lice raised concerns about the impact of rising sea surface temperatures on sea louse dynamics by showing that both high temperatures and increased temperature variation can increase the sea louse basic reproduction number, R 0 , and decrease generation time of sea lice, resulting in faster population growth [20]. The development of these mathematical models that incorporated environmental impacts has been facilitated by numerous laboratory studies that allowed for the parametrization of stage-specific effects of temperature on sea louse development [53].…”
Section: Management Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…We adapted a temperature profile from [27] for our simulations. This profile was derived by fitting a sine curve to daily temperature data from 33 salmon farms across 5 years in Scotland [31].…”
Section: Inputmentioning
confidence: 99%